Structure and luminescence study of nanoporous silicon layers with high internal surface - Makara, V.A.; Melnichenko, M.M.; Svezhentsova, K.V.; Khomenkova, L.Yu.; Shmyryeva, O.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
In this work, the technique of formation of homogeneous nanoporous silicon layers with high internal surface on solar cell substrates by stain etching is developed. Emission and structure properties of such layers were studied by photoluminescence (PL), photoluminescence excitation, Auger electronic spectroscopy, atomic force microscopy and scanning tunnel microscopy methods. It was observed that nanoporous layers are of high homogeneity and their thickness is ~20-25 nm. It was shown that the higher PL intensity of such layers in comparison with PL intensity of the layers prepared on standard substrates in the same regimes is connected with the higher internal surface. The increase of PL intensity during prolonged aging in air at the room temperature was observed.